A statistical analysis on the influence of process and solution properties on centrifugally spun nanofiber morphology - Atıcı, Bülin; Ünlü, Cüneyt H.; Yanilmaz, Meltem (SAGE Publications, 2021)
Centrifugal spinning is a fast and safe nanofiber production technique and polyacrylonitrile (PAN) nanofibers have been widely studied for many applications including energy storage, filtration, sensors, and biomedical applications. Nanofiber morphology, specific surface area, porosity and average fiber diameter are important to determine the performance of nanofibers in these fields. In centrifugal spinning, nanofiber morphology and average fiber diameter are influenced by solution properties and process parameters including rotational speed, feeding rate, collector distance, and nozzle diameter. In this study, the effect of solution concentration, rotational speed, feeding rate, collector distance and nozzle diameter on average fiber diameter and fiber morphology were studied and statistical analysis was performed to determine the main factors. Optimum solution and process parameters were determined as well. Increased average fiber diameter was seen with increasing polymer concentration and nanofibers produced at 4000 rpm with the feeding rate of 60 ml/h had the lowest average fiber diameter for all studied nozzle sizes (0.3 mm, 0.5 mm and 0.8 mm). 8 wt. % PAN solution was centrifugally spun with the rotational speed of 4000 rpm, feeding rate of 60 ml/h, collector distance of 20 cm and nozzle diameter of 0.3 mm and bead free nanofibers with the average fiber diameter of 680 ± 87 nm was observed.